2013
DOI: 10.1208/s12248-013-9531-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets and Mechanisms of Cancer Prevention and Treatment by Withaferin A, A Naturally Occurring Steroidal Lactone

Abstract: The plants used in Ayurvedic medicine, which has been practiced in India for thousands of years for the treatment of a variety of disorders, are rich in chemicals potentially useful for prevention and treatment of cancer. Withania somnifera (commonly known as Ashwagandha in Ayurvedic medicine) is one such medicinal plant whose anticancer value was realized over four decades ago after isolation of a crystalline steroidal compound (withaferin A) from the leaves of this shrub. The root and leaf extracts of W. som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 85 publications
2
109
0
Order By: Relevance
“…14,18,20,30 Accordingly we also found that WA treatment resulted in decreased expression of CDK1 but not cyclin B1 in both LY-10 and LY-3 cells lines, which may lead to G 2 /M phase arrest. Results of WA treatment on SudHL-6 cells were consistent with the G 2 /M phase arrest seen in melanoma, glioblastoma, and cervical cancer cells.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…14,18,20,30 Accordingly we also found that WA treatment resulted in decreased expression of CDK1 but not cyclin B1 in both LY-10 and LY-3 cells lines, which may lead to G 2 /M phase arrest. Results of WA treatment on SudHL-6 cells were consistent with the G 2 /M phase arrest seen in melanoma, glioblastoma, and cervical cancer cells.…”
Section: Discussionsupporting
confidence: 60%
“…Other groups have published similar findings on the inhibition of Akt and have suggested that it may be a result of WA targeting the intermediate filament, Vimentin. 13,14 To determine if inhibition of vimentin function is important in DLBCL, we examined the effect of another inhibitor of vimentin, Arylquin 1, which is thought to bind vimentin and induce Par-4 dependent apoptosis. 42 We found that cytotoxicity required 10 fold higher concentration of Arylquin 1 in DLBCL than shown in mouse embryonic fibroblasts and PC-3 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 WA targets the tumor proteasome, which leads to ubiquitinated protein accumulation and induction of ER stress in human cancer cells. 21,22 WA also has effects on autophagy, although the role of autophagy in the anticancer effects of WA remains to be determined.…”
Section: Introductionmentioning
confidence: 99%